Nutrient depletion and metabolic profiles in breast carcinoma cell lines measured with a label-free platform. (27th May 2015) - Demmel, F; Brischwein, M; Wolf, P; Huber, F; Pfister, C; Wolf, B
Abstract: The response of two well-characterized human breast cancer cell lines (MCF-7 and MDA-MB-231) to a series of nutrient deficiencies is investigated with a label-free cell assay platform. The motivation of the research is to analyze adaptive responses of tumor cell metabolism and to find limiting conditions for cell survival. The platform measures extracellular values of pH and dissolved oxygen saturation to provide data of extracellular acidification rates and oxygen uptake rates. Additional electric cell substrate impedance sensing and bright-field cell imaging supports the data interpretation by providing information about cell morphological parameters. A sequential administration of nutrient depletions does not cause metabolic reprogramming, since the ratios of oxygen uptake to acidification return to their basal values. While the extracellular acidification drops sharply upon reduction of glucose and glutamine, the oxygen uptake is not affected. In contrast to other published data, cell death is not observed when both glucose and glutamine are depleted and cell proliferation is not inhibited, at least in MCF-7 cultures. It is assumed that residual concentrations of nutrients from the serum component are able to maintain cell viability when delivered regularly by active flow like in the cell assay platform, and, in a similar way, under physiological conditions.